1999
DOI: 10.1111/j.1365-2400.1999.tb00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of hydraulic engineering on the dynamics and production potential of floodplain fish populations in Bangladesh

Abstract: The present paper examines the impact of hydraulic engineering on fish production potential in Bangladesh by comparing the population dynamics of six species sampled from floodplains inside and outside the Pabna Irrigation and Rural Development Project (PIRDP) during 1995 and 1996. All the sampled populations were dominated by a single cohort for most of the year. Recruitment occurred both inside and outside the flood control scheme, coinciding with floodplain inundation. The growth of all the six species was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 20 publications
3
55
5
Order By: Relevance
“…Therefore, this indicates that the pequira growth reduction is related to the decrease in temperature. In fact, under controlled experiment conditions, it is observed that the decrease in temperature can delay the growth of the fish (Lorenzen, 1996;Halls et al, 1999). The Moekhausia dichroura growth curve indicated that the recruitment -the entrance of a new cohort in the population -would occur in the middle of October, but there is no available information about the species reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this indicates that the pequira growth reduction is related to the decrease in temperature. In fact, under controlled experiment conditions, it is observed that the decrease in temperature can delay the growth of the fish (Lorenzen, 1996;Halls et al, 1999). The Moekhausia dichroura growth curve indicated that the recruitment -the entrance of a new cohort in the population -would occur in the middle of October, but there is no available information about the species reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Halls et al (1999) reported that the size at sexual maturity of female P. sophore in the Pabna Irrigation and Rural Development Project (PIRDP), Talimnagar Sluicegate, Pabna, Bangladesh was 6.1 cm TL. However, in a later study, Halls (2005) reported the size at sexual maturity of female P. sophore in the Lohajang river, Tangail, Bangladesh was 4.5 cm TL.…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that the extensive hydraulic engineering works associated with large-scale irrigation development have had a profound negative impact on many river ecosystems, which is reflected in a dramatic loss of biodiversity (Halls et al, 1999;Tomislav and Mitrofanov, 1998). Where this has resulted in loss of important subsistence fisheries, the impact of this change has generally been felt disproportionately by poor people.…”
Section: Introductionmentioning
confidence: 99%